Motives for gambling in sports betting among Gweru residents - Chikotora, Prince (Midlands State University, 2017)
The purpose of the study was to find the motives that influence gambling behaviour. The research also sought to find out the personal characteristics of gamblers and the outcomes they expect from gambling. The research was prompted by the rapid growth of gambling activities in Zimbabwe. The research is significant to institutions of learning and university students towards the learning of gambling motives. It is also significant to the society at large as it highlights aspects within the community that are motivating gambling and be able to eradicate this maladaptive behaviour. The study of motives for gambling among African populations will add vast knowledge towards the existing literature. The study adopted a quantitative approach to collect and analyse raw data obtained using questionnaires. The research also used descriptive survey design. Random sampling was administered on a total of 120 respondents. The raw data was analysed using the Statistical Package for Social Sciences (version 20) software and Microsoft excel software. The data was presented through pie charts and graphs and labelled by percentages. The main findings of the study concluded that gambling is motivated by three basic motives which are enhancement motives, social motives and coping motives. The research also found out that gamblers hope to get rich through gambling. The researcher overally concluded that gambling is a motivational consequence which is enhanced by high hopes of getting rich. The researcher recommends the inclusion of monetary motives to the gambling motives questionnaire.